TAMATSIL DALAM AL-QUR’AN (KAJIAN SENI RUPA DALAM KISAH NABI SULAIMAN) - Dilla Syafrina; Ali Akbar; Fikri Mahmud; Masyhuri Putra; Abd Wahid (Jurnal Pemikiran Islam, 2022)
This article discusses the nature of tamatsil in the story of Prophet Sulaiman. The word tamatsil in the Qur'an is found in two surahs, namely Saba' verse 13 and al-Anbiya' verse 52. the Saba' verse explains that the jinn was ordered by Prophet Solomon to make statues, the word used in this verse is finish. So, if the sentence in the verse is a command, it means that there is no prohibition against making it. But it is different again from the letter al-Anbiya 'verse 52. In that verse, the Prophet Ibrahim was surprised at his people who worshiped tamatsil. The choice of the word tamatsil in this study was due to two things. First, there is a public error in understanding the meaning of the tamatsil. Second, the Ministry of Religion often equates this word with the words shanam and watsan which means statue/idol, even though the three words have different meanings even though there are similarities. The results of this study can be concluded that the essence of tamatsil is something material, shaped, and illustrated which is usually used for decoration or toys. In Indonesia, the term tamatsil is known as duplicate or replica, such as key toys, children's toys in the form of humans, animals, or plants. The law of tamatsil is divided into two opinions, some allow it as long as it is not worshiped, and some forbid it even if it is not worshiped.